LEVELS OF KEY CYTOKINES, MACROGLOBULINS AND THEIR SPECIFIC IMMUNE COMPLEXES IN BLOOD SERA OF WOMEN TAKING COMBINED ORAL CONTRACEPTIVES - V. N. Zorina; E. V. Keremetskaya; L. G. Bagenova; R. M. Zorina (Медицинская иммунология)
Abstract. We investigated effects of combined oral contraceptives (COC) containing low- and microdoses of estrogenic components upon serum levels of macroglobulin family proteins (alpha-2-macroglobulin, α2-MG, and pregnancy-associated alpha-2-glycoprotein, α2-PAG), their immune complexes with IgG, as well as concentrations of some cytokines (IL-1β, IL-6, TNFα, IFNγ). It was shown that cytokine levels did not differ with control, whereas α2-MG concentrations showed a time-dependent decrease in a group of women taking COC with microdoses of estrogens, and α2-PAG levels increased tenfold, independent on dosage and time of COC application. Meanwhile, contents of PAG-IgG complexes exhibits a gradual decrease, along with increase in MG-IgG. Considering PAG as a marker of normal and malignant proliferation, we suggest, that the levels of α2-PAG may be useful in monitoring of women taking COC, in order to predict high risk of pathological  proliferation  by  evaluation  of  individuals with  elevated  α2-PAG  levels.  (Med.  Immunol.,  2011, vol. 13, N 6, pp 635-638)